Development of Flashcard Learning Media for Fourth Grade Science and Social Studies Subject - Maulinia Lestari; Tri Nopriana (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2025)
Learning that relies solely on textbooks often fails to capture students’ attention, leading to low engagement and suboptimal conceptual understanding. The use of flashcards as a learning medium for Science and Social Studies (IPAS) can be an effective solution, as they present information in a visual and concise manner, making it easier for students to grasp abstract concepts. Therefore, this study aims to develop flashcard-based learning media to improve students’ understanding of the concepts of climate and seasons. This research uses the Research and Development (R&D) method with the ADDIE development model (Analyze, Design, Develop, Implement, Evaluate); however, it is limited to the analysis, design, and development stages. The study utilized validation sheets as instruments, and validation was conducted by media and subject matter experts to assess the appropriateness and suitability of the flashcards as a learning tool. The media was validated by two media experts and one subject matter expert. The validation results showed a feasibility level of 98% from media experts and 98.75% from the subject matter expert, both falling into the